A study on selected demographic characteristics and mental health of young adults in public higher learning institutions in Malaysia - Md Nordin, Noradilah; Abu Talib, Mansor; Yaacob, Siti Nor; Sabran, Mohammad Shatar (Canadian Center of Science and Education, 2010)
Early adulthood is the transitional period between adolescence and adult life. As with other general young adult population, university students carry along several of life’s issues such as a personal and social adjustment, academic and career concerns, stress and other related psychosomatic issues which may lead to an unhealthy mental condition. These “life baggage” and stress must be managed well in order to prevent them from interfering with normal adult development and growth processes. The purpose of this study is to determine the association between several selected demographic characteristics and the mental health status of young adults studying in public Malaysian universities. A total of 1467 respondents were recruited using a multistage cluster sampling. General Health Questionnaire (GHQ-12) (Goldberg, 1978) was the research tool utilised to assess the undergraduates’ mental health status. Findings indicate that a majority of undergraduates exhibit a healthy mental state while a minority has some mental health concerns. One-way ANOVA tests showed that the mental health of undergraduates in this study differed in terms of ethnicity, year of study and academic field. In conclusion, these findings can assist student development personnel and academicians in enhancing their understanding of the current mental health status of undergraduate students and the demographic factors that relate to it.